"What we do is not actually journalism": Role negotiations in online departments of two newspapers in Slovenia and Serbia. (November 2014) - Vobič, Igor; Milojević, Ana
This study offers insights into articulations between the normative and the empirical in online journalists' self-negotiations concerning their roles in people's assimilation of information, the daily provision of news and their institutional status in online departments. In-depth interviews with online journalists from two leading newspapers, Delo in Slovenia and Novosti in Serbia, are used to investigate their negotiations with respect to their societal role. The analysis reveals troubled negotiation processes among interviewed online journalists when they consider what is regarded as "true" journalism, news production requirements and their institutional status. This indicates that rearrangements of political–economic relations in both post-socialist societies have increased journalism's responsibility to the media owners and power holders and surpassed its normatively defined responsibility to the public. Both case subjects are compared through the prism of the processes of negotiation of normative principles of journalism in the social, national and institutional contexts of the two newspapers.